La naturaleza de la poesía - Durão, Paulo Henrique (2020)
Sobre la casa del árbol de Estudio Botteri-Connell.
Keywords: CRITICA; ESTUDIO BOTTERRI-CONNELL ARQUITECTOS; BOTTERI CAPPA, SOFÍA; CONNELL, PATRICIO